Critical Thinking Skills Assessment Among Engineering Students - Noni, Nurul Shida; Abdullah, Abdul Halim (International Journal of Psychosocial Rehabilitation, 2020)
The level of critical thinking skills and its relationship to CGPA is investigated in this study. 80 men and 21 women from two engineering department at Polytechnic Ibrahim Sultan participating in this investigation. This research utilized The Malaysian Critical Thinking Skills Instrument-MyCT which consists of 60 items. Data analysis were performed using SPSS 22.0 for descriptive and inferential statistics. Comparative findings across studies revealed that the critical thinking level of engineering students at Polytechnic Ibrahim Sultan was intermediate (47.42%). The Mann-Whitney U test determines the variables between four categories in critical thinking skills and obtained no significant differences. The correlation of commuting between critical thinking skills as calculated with Spearman’s rho is not statistically significant. There was a negative weak correlation for analytical and logical (r=-0.098). Analysis of the computed findings revealed that the critical thinking is at a moderate level but weak in analytical and logical and disposition skills. In conclusion, lecturers must be more sensitive to this phenomenon, in which the emphasis on analytical and logical and disposition are important in teaching and learning.